Analysis of Allele Frequency Distribution Apoliprotein E Gene in Patients With Down Syndrome Trisomy 21 - Meinapuri, Malinda; Amir, Arni; Chundrayetti, Eva; efrida, efrida; Susmiati, Susmiati (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: Down syndrome is a global health problem of particular concern because people with Down syndrome have a wide variety of clinical disorders and are one of the causes of mental retardation and serious physical growth disorders.Down syndrome can occur at all socioeconomic, ethnic and demographic levels. The incidence of Down Syndrome will increase as the mother's age increases at the time of pregnancy and the incidence varies in different populations: 1 in 319 to 1 in 1000 live births. Each year, an estimated 3,000 to 5,000 children are born with Down syndrome. The APOE gene is located in the long arm (q) of chromosome 19 at position 13.2 (19q13.2). The APOE gene consists of four exons and three introns, a total of 3597 base pairs. In melanocyte cells APOE gene expression can be regulated by MITF. APOE is a form of polymorphic, which translates into three gene alleles: normal: allele ?3 and dysfunctional: allele ?2 and allele ?4.  The polymorphism of the APOE gene had a strong effect on the level of allele production, a high concentration of APOE indicated that the production of ?4 allele was increased and a low concentration of APOE was associated with the production of ?2 allelePurpose:To Analyze of Allele Frequency Distribution Apoliprotein E Gene  in Patients With Down Syndrome Trisomy  21Methods: This research is an analitic observasional study with a comparative  study design. The sample used was the result of DNA extraction patients with Down's Syndrome Trisomy 21 as many as 33 samples and 33 controls stored in the Biomedical Laboratory, Faculty of Medicine, Andalas University, Padang, Indonesia. The next step is to examine the APOE gene polymorphisms using PCR and sequencing techniques.Results: Samples of Down syndrome patients had variations in the distribution of alleles, where alleles ?4 and ?2 were found even though the allele frequency ?3 was still the highest allele frequency. Meanwhile, in the samples representing the normal control population, ?3 and ?2 alleles were found and no ?4 allele was found. Although the allele is not associated with Down Syndrome, Down Syndrome sufferers have a 2.26 times greater risk for e2 and e4 alleles than e3.Conclusion: There was a difference in the frequency distribution pattern of the APOE gene allele in patients with Down Trisomy Syndrome 21 compared to the control.